FABRICATION OF UNGLAZED CERAMIC TILE USING DENSE STRUCTURED SAGO WASTE AND CLAY COMPOSITE - Aripin Aripin; S. Tani; S. Mitsudo; T. Saito; T. Idehara (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2010)
FABRICATION OF UNGLAZED CERAMIC TILE USING DENSE STRUCTURED SAGOWASTE AND CLAY COMPOSITE. In Indonesia, the sago processing industry generates every year huge amount of sago waste, and converting this waste into a useful material is possible. In the present study, physical properties of dense structured sago waste and clay composite were investigated in order to study the feasibility of reuse this sample as raw material in the producing of ceramics. Firstly, the chemical composition of ash (obtained from the sago waste) and clay was characterized. The prepared sample was sintered at the temperature range from 800 to 1,200 oC using electric furnace. The density, linear shrinkage and water absorption of the sintered sample were determined by using the Archimedes' method. The experimental result indicated that the density of the sintered sample increased with increasing sintering temperature up to 1100oC and then slightly decreased afterward. The water absorption of the products decreased with an increase in sintering temperature. In the sintered sample at 1,100 oC, the water absorption decreased rapidly and water adsorption of less than 1% was achieved. This water absorption was less than 5% which was needed for unglazed floor tile. The result of water adsorption suggest that it is possible to use this sample as a raw material for producing the ceramic floor tile.